Calculate the sum of:
Notation: denotes the GIF/Floor Function .
This problem has been adapted with slight modifications from the COMC 2000.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We note that ⌊ n ⌋ = k for k 2 ≤ n ≤ ( k + 1 ) 2 − 1 , where n and k are positive integers, and we have ( k + 1 ) 2 − k 2 = 2 k + 1 such n . Therefore the sum:
n = 1 ∑ 1 4 5 ⌊ n ⌋ = n = 1 ∑ 1 2 2 − 1 ⌊ n ⌋ + n = 1 4 4 ∑ 1 4 5 ⌊ n ⌋ = k = 1 ∑ 1 1 k ( 2 k + 1 ) + ⌊ 1 4 4 ⌋ + ⌊ 1 4 5 ⌋ = k = 1 ∑ 1 1 ( 2 k 2 + k ) + 1 2 + 1 2 = 2 ⋅ 6 1 1 ( 1 2 ) ( 2 3 ) + 2 1 1 ( 1 2 ) + 2 4 = 1 0 1 2 + 6 6 + 2 4 = 1 1 0 2